RESPON KONSUMEN TERHADAP PRODUK MAKANAN INSTAN - Widodo, Tri (AMONG MAKARTI, 2013)
Abstract Fast food is the food is packaged , easy to prepare , practical , or treated in a simple way . The food is generally produced by the food processing industry with high technology and provide a variety of additives to preserve and provide flavor to the product . Fast food is usually in the form of side dishes in packs , instant noodles, nuggets, or even corn flakes as food for breakfast. World Health Organization ( WHO ) and the Food and Agricultural Organization ( FAO ) states that the potential threat of food residues on human health are divided into 3 categories , namely : 1)  toxicological aspects, 2) microbiological aspects, 3) imunopatologis aspects. Some of the negative effects of fast food are as follows : Increase the Risk of Heart Attack, Making Addicted, Enhance Weight Loss, Increases Cancer Risk, Trigger Diabetes, High Blood Pressure Triggering. Based on survey results, consumers generally a little more knowing that instant food or fast food often called the impact on health is not good , but for various reasons and considerations so forced and also must consume the fast food. It required the cooperation of all parties to avoid or at least minimize the impact of fast food or instant food on the health of consumers. Cooperation is required on the part of the consumer, the consumer must be selective and carefully selecting and sorting , where healthy food is consumed and where to eat less healthy or even harmful to health . Parties participating manufacturers must keep maintaining the health of the consumer , be careful in producing processed foods , should choose materials that are not harmful to health , must comply with the rules in force , not only concerned with their interests so that consumer interests are ignored . Goods sold are not worthy to be discarded or removed and not sold. Salatiga government should also play an active role in this regard . Taking into account the interests of consumers and also the interests of producers . Always keep an eye on the circulation of goods in the market , especially Pasar Raya I, always keep an eye on the manufacturer , control products are sold . Keywords : Consumer Response , instant food products